2012
DOI: 10.1002/tox.21752
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to 17α-ethinylestradiol decreases motility and ATP in sperm of male fighting fishBetta splendens

Abstract: The synthetic estrogen 17α-ethinylestradiol (EE2) is an endocrine-disrupting chemical released into aquatic environments from sewage treatment facilities. We tested the effects of two environmentally relevant concentrations of waterborne EE2, 10 and 100 ng L(-1) , on reproductive endpoints in the teleost fish Betta splendens. In the first experiment, testes were removed from males and sperm were exposed to EE2 directly through the activation water. Direct exposure to EE2 had no effect on any measure of sperm s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 102 publications
(143 reference statements)
2
15
0
Order By: Relevance
“…Greater exposure duration than 21 days or exposure to combinations of other chemicals in wood pulp mill effluent might produce an effect, as suggested by other researchers [58]. Although previous work found decreased sperm quality [42] and aggression [26] in male B. splendens exposed to phytoestrogens, the results of the present study reflect the assertion made previously [30] that B. splendens may be more resistant to phytoestrogens than previously thought.…”
Section: Discussionsupporting
confidence: 86%
“…Greater exposure duration than 21 days or exposure to combinations of other chemicals in wood pulp mill effluent might produce an effect, as suggested by other researchers [58]. Although previous work found decreased sperm quality [42] and aggression [26] in male B. splendens exposed to phytoestrogens, the results of the present study reflect the assertion made previously [30] that B. splendens may be more resistant to phytoestrogens than previously thought.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, DiNP altered the sperm quality after 21-day treatment, affecting the percentage of motile cells over time after activation, compared to the POST-CTRL treatment. Decreased sperm swimming velocity in terms of VSL, GSI and sperm density were observed in fighting fish Betta splendens after exposure with 17α-ethinylestradiol (EE2) for four weeks and the same trend was observed for the percentage of motile cells and VCL (Montgomery et al, 2014). In the same study, reduced ATP content was found in the EE2 treated group, assuming reduced swimming velocity and therefore reduced fertilizing capacity, since the higher ATP content means a higher proportion of motile spermatozoa (Vladić and Järvi, 2001).…”
Section: Discussionmentioning
confidence: 52%
“…Experiments in adult males of medaka demonstrated that sperm velocity increased with a rise in the duration of EE 2 exposure (above 60ng/L), while the fertilization rate was reduced (Hashimoto et al, 2009). However, the activation of sperm in water with EE 2 (10 or 100 ng/L) did not affect sperm motility in Beta splendens (Montgomery et al, 2012).…”
Section: Discussionmentioning
confidence: 79%
“…It is because of the nature of this fertilization that the first minute after induction of motility is crucial for success (Casselman et al, 2006;Hara et al, 2007) and, the sperm must swim fast enough and in the right direction to find the micropyle (Rurangwa et al, 2004). Thus, sperm motility is a reliable indicator of fertilization success in fishes (Rurangwa et al, 2001;Fitzpatrick et al, 2009), and the presence of any contaminant in the water that affects this direction may be harmful to the fertilization process (Montgomery et al, 2012).…”
Section: Introductionmentioning
confidence: 99%